2004
DOI: 10.1152/ajprenal.00272.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonicity and TonEBP promote development of the renal concentrating system

Abstract: DESPITE SEVERE HYPEROSMOTIC stress imposed by NaCl and urea on cells of the renal medulla, the elevated and highly variable osmolality in this part of the kidney is necessary for proper function of the urinary concentrating mechanism. This mechanism develops only after birth, and newborn rats are incapable of producing concentrated urine (13). Depending on hydration state, renal medullary osmolality of adult rats ranges from 500 to Ͼ2,500 mosmol/kgH 2 O as a result of elevated salt and urea concentrations. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…This also suggested that AR expression has to precede the initiation of the development of the urine concentrating mechanism, a finding that is consistent with previous AR developmental expression studies (39). As suggested by others (19,24), local hypertonicity and cell shrinkage could be important triggering factors for renal cell apoptosis during kidney development. Indeed, apoptosis was suggested to be part of the mechanism for lengthening of the thin ascending limb and the separation of the inner and outer medulla (19).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This also suggested that AR expression has to precede the initiation of the development of the urine concentrating mechanism, a finding that is consistent with previous AR developmental expression studies (39). As suggested by others (19,24), local hypertonicity and cell shrinkage could be important triggering factors for renal cell apoptosis during kidney development. Indeed, apoptosis was suggested to be part of the mechanism for lengthening of the thin ascending limb and the separation of the inner and outer medulla (19).…”
Section: Discussionsupporting
confidence: 88%
“…Urine osmolality rises from 300 mosmol/kgH 2 O at birth to nearly 2,000 mosmol/ kgH 2 O by the age of 3 wk (39). The maturation of this mechanism is believed to be developmentally regulated and may be regulated by corticosteroid hormones (37) and/or hypertonicity and the osmoresponsive transcriptional factor tonicity-responsive element binding protein (TonEBP)/osmotic response element binding protein (OREBP) (15,24), the latter being the only known osmotic-responsive transcriptional activator. Loss of TonEBP/OREBP resulted in renal atrophy and lack of tonicity-responsive gene regulation, defective urine concentration, and the development of polyuria and polydipsia (28).…”
mentioning
confidence: 99%
“…However, under physiological conditions, hyperosmolarity induces renal cell differentiation and the maturation of urine concentrating system. Moreover, variation of interstitial osmolality is necessary to concentrate urine in mature kidneys [14,17,33]. Interestingly, both situations require an active lipid metabolism: as a protective mechanism against osmotic stress for preserving membrane structure and as a physiological tool for constructing cell structure and tissue architecture of differentiated cell state.…”
Section: Discussionmentioning
confidence: 99%
“…to trigger adaptive responses to survive [13,14]. In addition, hyperosmolarity is a main signal for renal tubular cells differentiation [15][16][17]. Former works from our laboratory showed that the renal inner medullary cells possess the most dynamic phospholipid synthesis and membrane turnover among the various kidney zones [18,19].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation